Philosophy of Science In The Scope of Ontology, Concepts and Objects of Science - Indri Pangastuti; Yang Meng; Sofyan Sauri (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Systematic philosophy broadly includes, namely; Ontology or essence theory which discusses the nature of everything that gives rise to knowledge, epistemology or theory of knowledge which discusses how we obtain knowledge, and axiology or value theory which discusses the use of knowledge (Juanda, 2016). These three theories actually discuss the same nature, only starting from different things and goals. The purpose of this writing is to explain science in terms of philosophy from an ontological perspective, and to find out how objects and concepts are in science. In writing this article, we used the literature study method or carried out studies from various books and other scientific works related to the topic raised.